Heat-induced formation of reactive oxygen species and 8-oxoguanine, a biomarker of damage to DNA - Bruskov, Vadim I. (Oxford University Press, 2002)
Heat-induced formation of 8-oxoguanine was demonstrated in DNA solutions in 10(–3) M phosphate buffer, pH 6.8, by enzyme-linked immunosorbent assays using monoclonal antibodies against 8-oxoguanine. A radiation-chemical yield of 3.7 × 10(–2) µmol J(–1) for 8-oxoguanine production in DNA upon γ-irradiation was used as an adequate standard for quantitation of 8-oxoguanine in whole DNA. The initial yield of heat-induced 8-oxoguanine exhibits first order kinetics. The rate constants for 8-oxoguanine formation were determined at elevated temperatures; the activation energy was found to be 27 ± 2 kcal/mol. Extrapolation to 37°C gave a value of k(37) = 4.7 × 10(–10) s(–1). Heat-induced 8-oxoguanine formation and depurination of guanine and adenine show similarities of the processes, which implies that heat-mediated generation of reactive oxygen species (ROS) should occur. Heat-induced production of H(2)O(2) in phosphate buffer was shown. The sequence of reactions of thermally mediated ROS formation have been established: activation of dissolved oxygen to the singlet state, generation of superoxide radicals and their dismutation to H(2)O(2). Gas saturation (O(2), N(2) and Ar), D(2)O, scavengers of (1)O(2), O(2)(–•) and OH(•) radicals and metal chelators influenced heat-induced 8-oxoguanine formation as they affected thermal ROS generation. These findings imply that heat acts via ROS attack leading to oxidative damage to DNA.